Estudo técnico e econômico do uso do sistema de irrigação por gotejamento na cultura do cafeeiro (Coffea arábica L.) - Silva, Adriana Lúcia da (2002)
The general goal ofthis work was the technical and economical evaluation of the use ofdrip irrigation system in a coffee crop in the region ofLavras - MG, in any case had as interest verify ifthe irrigation is a technology that changes the quality of drink of the coffee, without burdening producer's pocket. The analyzed data were obtained from an experiment carried out in Lavras - MG using the cultivar "Acaiá Cerrado"(M(j 1474), growing ina spacing of3,0 mx 0,6 m. The experimental delineation was randomized blocks split in treatments corresponding to 5 irrigation water depth (L0 = without irrigation, LI = 100%, L2= 80%, L3 = 60% and L4 = 40% ofthe Evaporation from the Class A Pan Evaporimeter - ECA) and 3 splitting ofN and K(3, 6 and 9 times) in the period from October to March. In order to determine the quality of the harvested grains, anaryses of the quality ofthe drink ofthe coffee were done by the chemical methods and "proof of cup", besides the classification for sieves and classifícation for kind. For accomplishment ofthe economic analysis it was used the production data of 3 combined harvest, 1998/1999, 1999/2000 and 2000/2001. The analyze of irrigated farming costs was based in the theory of costs of production. Considering the applied methodology, one can conclude that the expenses with the variable resources were the ones that burdened most the final cost of the coffee in ali treatments ofirrigation. The items that affected most the production costs were machines and implements, in the case of the fixed resources, and the expenses with materiais, in the case of the variable resources. There was a good efficiency technique likewise the productrve average ofthe treatments was 54 sacks for hectare. The irrigation water depth with 100% of the Evaporation from the Class A Pan Evaporimeter had productrve average of68 sacks for hectare. It was also concluded that there was no influence ofthe drip irrigation in the quality ofthe drink ofthe coffee and the economic analysis was considered the price of the coffee in R$120,00, and, in these conditions, it is recommendable the adoption of the treatment with replacement of100% ofthe ECA.